Interview with Juan Francisco Delgado Ruiz, former president of the Spanish Confederation of Fathers and Mothers (CEAPA) - González-Moreno, Javier (Historia y Memoria de la Educación, 2023)
Since its foundation in 1979, the Confederación Española de Asociaciones de Padres de Alumnos (CEAPA) groups together the majority of parent associations of students from public schools in our country, thus becoming one of the most important organizations in the Spanish education. In this interview, we talked with Juan Francisco Delgado Ruiz, who was an important director of CEAPA for many years, about its birth and its evolution, as well as its influence on educational policy and its relationship with the secularization of our educational system. Also we talked about the previous experience of Juan Francisco Delgado Ruiz in the Socialist Party and his later experience in Europa Laica, organizations also related to the secularization and secularism of education.